KOMUNIKASI POLITIK EDY MULYADI DALAM AKUN YOUTUBE PRIBADI KAJIAN PERSONALISASI: KAJIAN PERSONALISASI DAN STRATEGI KOMUNIKASI - Annisa Fatika; Anisa Fitri; Nurhalijah Patonah Siregar; Ibrahim Naufik; Ripqi Ramadhan Harahap; Muhamad Dimas Nugroho (AT-TAWASUL, 2025)
his study explores Edy Mulyadi’s political communication on his personal YouTube channel by focusing on two core aspects: political personalization and alternative communication strategy. A descriptive qualitative design combined with Fairclough’s Critical Discourse Analysis was employed. Data were collected from 5–10 politically relevant videos using non-participant observation, verbatim transcription, visual documentation, and audience-comment analysis. Findings reveal that Edy constructs a personalized political identity by presenting himself as a spokesperson for marginalized communities through emotive language, Islamic symbols, casual attire, and physical proximity to grassroots subjects. He avoids party emblems, emphasizes authenticity, and cultivates an anti-elite image. His strategy is alternative: YouTube functions as a counter-hegemonic arena, free from mainstream media and party control, enabling unfiltered critiques of oligarchy, corruption, and social inequality to circulate widely. The resulting discourse underscores distributive justice, religious values, and inclusive nationalism. These insights demonstrate the capacity of digital media to operate as a site of political resistance and show that personalization can be an effective tool for fostering public trust within contemporary digital democracy.